ANALISIS TINGKAT PEMAHAMAN PENDIDIKAN SEKSUAL PADA ANAK SEKOLAH DASAR - Dwinata, Anggara; Nuruddin, Muhammad; Rahma Pratiwi, Emy Yunita; Susilo, Claudya Zahrani; Hardinanto, Eko (Jurnal Kajian Pembelajaran dan Keilmuan, 2024)
Sex education is very important to convey to people, including elementary school students. Sex education aims to provide information about the truth and understanding of everything related to sexuality, so that in the future when students grow up they can live a social life properly and correctly according to the knowledge they gained while at school. The urgency of sex education is given to elementary school children so that children can prevent and minimize the impact of sexual harassment which is currently rampant. This research is a literature review study with the topic of discussion, namely understanding elementary school students' sex education. Based on the results of the review, it provides unique findings regarding sex education in elementary schools. These findings provide an understanding that: 1) the level of parental education has an impact on the level of understanding of children's sexuality, 2) parents have a role in preventing sex that occurs in elementary school children, 3) communication between parents and children must be established in harmony as a form of development children's sexuality period, and 4) educational institutions must be aware that sex education needs to be provided when children are at primary school age with adapted material.